Metabolism of aflatoxins: key enzymes and interindividual as well as interspecies differences - Dohnal, Vlastimil; Wu, Qinghua; Kuča, Kamil (Archives of toxicology, 2014)
Aflatoxins are potent hepatocarcinogen in animal models and suspected carcinogen in humans. The most important aflatoxin in terms of toxic potency and occurrence is aflatoxin B1 (AFB1). In this review, we mainly summarized the key metabolizing enzymes of AFB1 in animals and humans. Moreover, the interindividual and the interspecies differences in AFB1 metabolism are highly concerned. In human liver, CYP3A4 plays an important role in biotransforming AFB1 to the toxic product AFB1-8,9-epoxide. In human lung, CYP2A13 has a significant activity in metabolizing AFB1 to AFB1-8,9-epoxide and AFM1-8,9-epoxide. The epoxide of AFB1-8,9-epoxide could conjugate with glutathione to reduce the toxicity by glutathione-S-transferase (GST). In poultry species, CYP2A6, CYP3A37, CYP1A5, and CYP1A1 are responsible for bioactivation of AFB1. There are interindividual variations in the rate of activation of aflatoxins in various species, and there are also differences between children and adults. The age and living regions are important factors affecting resistance of species to AFB1. The rate of AFB1-8,9-epoxide formation and its conjugation with glutathione are key parameters in interspecies and interindividual differences in sensitivity to the toxic effect of AFB1. This review provides an important information for key metabolizing enzymes and the global metabolism of aflatoxins in different species.
Keywords: Liver; Reproducibility of Results; játra; toxikokinetika; systém (enzymů) cytochromů P-450; Endoplasmic Reticulum; Carcinogens, Environmental; endoplazmatické retikulum; reprodukovatelnost výsledků; aflatoxin B1; Toxicokinetics; Inactivation, Metabolic; Intestinal Mucosa; Cytochrome P-450 Enzyme System; metabolická inaktivace; Respiratory Mucosa; Aflatoxin B1; zvířata; plíce; Humans; Species Specificity; střevní sliznice; respirační sliznice; druhová specificita; Lung; karcinogeny životního prostředí; lidé; Animals